2017
DOI: 10.22354/in.v21i2.650
|View full text |Cite
|
Sign up to set email alerts
|

Traqueobronquitis y neumonía asociadas a ventilación mecánica en unidades de cuidado intensivo de Latinoamérica: epidemiología, curso clínico y desenlaces (Estudio LATINAVE)

Abstract: Cómo citar este artículo: Varón-Vega FA, et al. Traqueobronquitis y neumonía asociadas a ventilación mecánica en unidades de cuidado intensivo de Latinoamérica: epidemiología, curso clínico y desenlaces (Estudio LATINAVE). Infectio 2016. http://dx.doi.org10.22354/in.v21i2.650 ResumenIntroducción: Las infecciones asociadas a ventilación mecánica son causa importante de morbimortalidad en el paciente crítico. La diferenciación entre traqueobronquitis y neumonía no es siempre fácil, y es controvertida. Algunos tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The results found in this study showed a high microbial resistance to the most antibiotics tested, and presented quite similarity when compared to the data reported by Ju et al [27], Varon-Vega et al [28] and Seibert [29], since the most prevalent gender was the masculine. On the other hand, in a study conducted by Bezerra et al [14] that followed 74 patients, the majority of them was women.…”
Section: Discussionsupporting
confidence: 89%
“…The results found in this study showed a high microbial resistance to the most antibiotics tested, and presented quite similarity when compared to the data reported by Ju et al [27], Varon-Vega et al [28] and Seibert [29], since the most prevalent gender was the masculine. On the other hand, in a study conducted by Bezerra et al [14] that followed 74 patients, the majority of them was women.…”
Section: Discussionsupporting
confidence: 89%